›satura‹ - Monströses Schreiben in Antike und Aufklärung Lucilius, Varro, Horaz, Petron, Martianus Capella, Hamann, Jean Paul - Dell'Anno, Sina (Theorie der Prosa, 2023)
Under the name satura, this volume examines a "monstrous" text tradition characterized by mixed forms and intertextual hypertrophy. In studies on authors like Lucilius, Varro, Horace, Petronius, Hamann, and Jean Paul, Sina Dell'Anno takes a new perspective on this tradition by focusing her attention on the notorious formlessness of satirical texts as the engine of her autophilological poetics.